Effect of non-uniform magnetic field on combustion products of aluminum nanopowder in mixture with titanium and zirconium dioxides; Materials Letters; Vol. 346 - Amelkovich Yu. A. Yuliya Alexandrovna (2023, 2023)
Title screen